Explaining African Economic Performance - Collier, Paul; Gunning, Jan Willem (Journal of Economic Literature, 1999)
Africa has had slow growth and a massive exodus of capital. In many respects it has been the most capital-hostile region. We review and interpret the aggregate-level and microeconomic literatures to identify the key explanations for this performance. There is a reasonable correspondence of the two sets of evidence, pointing to four factors as being important. These are a lack of openness to international trade; a high-risk environment; a low level of social capital; and poor infrastructure. These problems are to a substantial extent attributable to government behavior, and the paper includes a review of the political economy literature addressing that behavior.